2018
DOI: 10.1002/ccd.27491
|View full text |Cite
|
Sign up to set email alerts
|

One‐year clinical outcomes and multislice computed tomography angiographic results following implantation of theNeoVas bioresorbable sirolimus‐eluting scaffold in patients with single de novo coronary artery lesions

Abstract: This study demonstrated the safety and efficacy of the NeoVas scaffold for patients with single de novo coronary artery lesions at 1 year of follow-up. Noninvasive MSCT data confirmed vessel patency and the maintenance of vessel dimensions following implantation of the NeoVas bioresorbable sirolimus-eluting scaffold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Second, two recent meta-analyses [ 28 , 29 ] showed ABSORB bioresorbable coronary stents to be associated with increased risk of stent thrombosis and target lesion failure (target vessel myocardial infarction and lesion revascularisation), in comparison to cobalt-chromium everolimus-eluting metallic stents. Despite these results, improvements can be expected from newer scaffold designs with thinner struts (125 μm and less) [ 30 , 31 ], eluting drugs other than everolimus [ 32 ], dedicated implantation protocols [ 13 ], optimized lesion and patient selection, as well as modified antithrombotic therapy protocols [ 33 ]. In this context, feasibility of intrastent CT imaging makes the latter a valuable noninvasive tool for assessment of new BRS technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, two recent meta-analyses [ 28 , 29 ] showed ABSORB bioresorbable coronary stents to be associated with increased risk of stent thrombosis and target lesion failure (target vessel myocardial infarction and lesion revascularisation), in comparison to cobalt-chromium everolimus-eluting metallic stents. Despite these results, improvements can be expected from newer scaffold designs with thinner struts (125 μm and less) [ 30 , 31 ], eluting drugs other than everolimus [ 32 ], dedicated implantation protocols [ 13 ], optimized lesion and patient selection, as well as modified antithrombotic therapy protocols [ 33 ]. In this context, feasibility of intrastent CT imaging makes the latter a valuable noninvasive tool for assessment of new BRS technologies.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis published on Lancet in 2017 showed that coronary artery diameter <2.25 mm and female sex were independent risk factors for in-stent thrombosis. [16] In 2018, Wang et al [17] conducted an observation of 31 cases implanted with NeoVas scaffold in PCI over a 1-year period and reported no cardiac death or in-stent thrombosis, except for 1 case who suffered recurrent ischemic events. This finding supports the implantation of NeoVas scaffold as demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from First-in-man study, randomized clinical trial (RCT) and single-arm trial (NeoVas registry) have confirmed the efficacy and safety of the device for the treatment of patients with noncomplex coronary lesions. [11][12][13][14] The Chinese National Medical Products Administration (NMPA) had approved the NeoVas BRS to treat coronary artery disease on February 26, 2019.…”
Section: Introductionmentioning
confidence: 99%